The association between alcohol exposure and self-reported health status: The effect of separating former and current drinkers - Liang, Wenbin; Chikritzhs, Tanya (Public Library of Science, 2013)
Aims: To investigate the direction and degree of potential bias introduced to analyses of drinking and health status which exclude former drinkers from exposure groups. Design: Pooled analysis of 14 waves (1997–2010) of the U.S. National Health Interview Survey (NHIS). Setting: General population-based study. Participants: 404,462 participants, from 14 waves of the NHIS, who had known self-reported health status and alcohol consumption status. Measurements: Self-reported health status was used as the indicator of health. Two approaches were used to classify alcohol consumption: (i) separation of former drinkers and current drinkers, and (ii) combined former and current drinkers. The prevalence of fair/ poor health by alcohol use, gender and age with 95% confidence intervals was estimated. The difference in prevalence of fair/ poor health status for lifetime abstainers, former drinkers, current drinkers and drinkers (former drinkers and current drinkers combined) were compared using Poisson regression with robust estimations of variance. Findings: Excluding former drinkers from drinker groups exaggerates the difference in health status between abstainers and drinkers, especially for males. Conclusions: In cohort study analyses, former drinkers should be assigned to a drinking category based on their previous alcohol consumption patterns and not treated as a discrete exposure group.